Full Mouth Rehabilitation of a Patient with Uneven Occlusal Plane and Severe Attrition: A Clinical Report - Abhilash Mohapatra1, Sitansu Sekhar Das1, Gunjan Srivastava1, Pradyumna Kumar Sahoo2, Upsana Dhar3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In clinical practice we usually come across cases with severe tooth wear which requires a full mouthrehabilitation. And management of patients with worn-out dentition was always a tough and complexprocedure. For a predictable and favourable treatment outcome a systemic multidisciplinary approach wasrequired. This case report describes the interdisciplinary approach in the treatment of a patient with severeattrition and loss of vertical dimension. After performing endodontic treatment for required teeth, a biteraising transitional prosthesis was given for increasing the VD to acquire essential interocclusal space forpost and core buildups and full coverage restorations. After that the porcelain fused to metal permanentrestoration was fabricated and scrutinized for stable contact in centric and eccentric relation.